Kekuasaan dan Moral dalam Pandangan Politik Niccolo Machiavelli - Mukhtar, Mukhtar (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
This study discusses the concept of understanding the moral hearts political views Power Niccolo Machiavelli. Complete named Leonardo Niccolo Machiavelli was born in Florence (Firenze), Italy, 3 May 1469 and commonly referred to by name in the